The One Before the Many: Towards a Simmelian Sociogenesis - Kneubühler, Marine (Simmel Studies)

(untitled) (Edizioni ETS, 2025)
This article recovers a principle central to Simmel’s sociology yet largely overlooked: the quantitative, or numerical, determination of social forms. Read as the basis for a genuine sociogenesis, this principle first lets us unsettle the dichotomous typologies on which classical sociology was founded, replacing fixed historical types with a continuous, threshold-sensitive scale that governs both the differentiation of individuals and the normative order that binds them. Pursued to its own logical end, however, this same principle requires a further descent, from three to two to one, that challenges an influential recent reading of Simmel – Gilbert’s claim that the dyad forms sociology’s minimal unit – and locates the group’s least common denominator in the individual as such, apart from the legacies of individualization and individualism.